Analisis Kelayakan Usaha UMKM Laundry “Seuseuhan” - Adriana Putri D; Nabila Nuzhatul F; Danish Nayyara Putri; Sikla Alfathlaily Suteja; Najwa Anjani Nurizkita; Antonya Rumondang Sinaga; Farida Ratna Dewi; Sari Heviawati; Novia Rahmawati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Small businesses play an important role in the Indonesian economy, including the service sector such as laundry, which requires good management to ensure sustainability and operational efficiency. This research was conducted on a laundry business located at Jl. Malabar Ujung No.34, RT.2/RW.07, Babakan, Bogor Tengah District, Bogor City, West Java. This research aims to analyze the financial feasibility of the laundry business